Cover Feature: Synthesis of Cyclen‐Functionalized Ethenylene‐Based Periodic Mesoporous Organosilica Nanoparticles and Metal‐Ion Adsorption Studies (ChemNanoMat 11/2020). Issue 11 (15th October 2020) - Li, Hao; Vardanyan, Ani; Charnay, Clarence; Raehm, Laurence; Seisenbaeva, Gulaim A.; Pleixats, Roser; Durand, Jean‐Olivier
Abstract : Why would heavy metal ever go away? Cyclen‐functionalized ethenylene‐based periodic mesoporous organosilica nanoparticles were prepared for heavy metal removal from model solutions. The kinetics and isotherms of adsorption of nickel and cobalt were determined, and these nanomaterials showed high uptake of metals (up to 3.9 mmol g −1 ). They demonstrated pronounced selectivity in the separation of rare earth elements (e.g., neodymium and samarium) from late transition metals, e.g. Ni(II) and Co(II), by adsorption and even more so by controlled desorption. More information can be found in the Full Paper by Jean‐Olivier Durand, Roser Pleixats, Gulaim Seisenbaeva et al.